Abel Viana (1896-1964): uma vida de arqueólogo - Cardoso, João Luís (Estudos Arqueológicos de Oeiras, 2014)
In this article we present a synthesis of the work of Abel Viana (1896-1964) in the Archaeology. We stress the existence of three phases in his career, corresponding to an increase and diversity of his scientific production: the initial phase, developed in his native region (Minho, Northern Portugal); the second phase, corresponding to the period he stayed in Faro, Algarve; and the last phase, when he lived in Beja (Baixo Alentejo), where he wrote his most important works.